Software as a Service for Data Scientists. - Allen, Bryce; Bresnahan, John; Childers, Lisa; Foster, Ian; Kandaswamy, Gopi; Kettimuthu, Raj; Kordas, Jack; Link, Mike; Martin, Stuart; Pickett, Karl; Tuecke, Steven (Communications of the ACM, 2012)
Globus Online manages fire-and-forget file transfers for big-data, high-performance scientific collaborations. INSET: Other Approaches.